Akademickie batalie. Tradycje i współczesność - Drozdowicz, Zbigniew (Człowiek i Społeczeństwo, 2021)
In these remarks I make the attempt to sketch a battle which in the time span of many centuries had been led by the academic community with the internal and external threats. The first ones included (and still do in large extent) among others interfering in the conducted scientific research by the Church authorities. The latter ones on the other hand included crossing the boundary of science and stepping into the territory infested by all sorts of pseudoscience. Although I recall here just the example of such pseudoscience such as alchemy, but nevertheless it shows well how hard it was and still is for scholars to set these boundaries and not to cross them. In the end of the paper I formulate certain general remarks and suggestions related to the issues tackled in the text.